Enquêtes d’aujourd’hui sur les explorations polaires d’autrefois : le récit d’une expédition en Arctique dans "Un monde sans rivage" d’Hélène Gaudy - Pagès, Laurent (HAL CCSD, 2021)
International audience In "Un monde sans rivage" (2019), Hélène Gaudy recounts Andrée’s Arctic balloon expedition of 1897, a failed attempt to reach the North Pole. This article focuses first on the reasons that prompted the novelist to investigate a well-known expedition of the past, which proved to be an inexhaustible source of information. It then studies how the novel deals with the quantitative and qualitative insufficiency of the expedition’s traces by proposing a narrative that questions its sources, and presents itself as hypothetical. Finally, the article shows how Hélène Gaudy combines an archaeological approach with ecological considerations in order to explore representations, uses, and successive states of the Arctic.